Paparazzi media practices and celebrity culture - McNamara, Kim (Polity, 2016)
Paparazzi photography has emerged as a key element in today s media landscape. This book charts the historical and cultural significance of the industry, profiles its protagonists and discusses how its imagery of celebrity have become a major part of media consumption.